Instant Pot miracle vegetarian cookbook : more than 100 easy meatless meals for your favorite kitchen device - Pitre, Urvashi (Houghton Mifflin Harcourt, 2020)
"100+ all-new meatless recipes for the Instant Pot by the best-selling author of Indian Instant Pot and Instant Pot Fast & Easy."--